PENGEMBANGAN PROGRAM BIMBINGAN BELAJAR MATEMATIKA UNTUK SISWA SMP DI DESA NANOWA - Serupa Laia (Universitas Nias Raya, 2023)
This community service activity aims to develop a mathematics tutoring program for junior high school students in Nanowa Village. The program is designed to enhance students' understanding of mathematical concepts and to motivate them in their studies. Through a participatory approach, students, parents, and teachers are involved in an interactive and enjoyable learning process. The methods employed include problem-based learning, collaborative activities, and the use of various learning media. The results of this activity show a significant increase in students' understanding of mathematics, greater interest in learning, and increased parental involvement in their children's education. This program is expected to have a lasting positive impact on students and the community of Nanowa Village, as well as to serve as a model for similar programs in other areas.